A Karenina Companion - Turner, C. J. G. (Book collections on Project MUSE., 2006)
Although Anna Karenina has been described as "the European novel" by Frank Leavis, the geographical setting of the novel and, increasingly, its temporal and cultural setting, render it a foreign novel to most readers. A Karenina Companion offers a wealth of information, including a great deal that has previously not been available in English, for the scholarly and literary appreciation of this great novel. Chapter 1 is a biographical introduction and Chapter 2 an examination of the way in which the novel was composed. In Chapter 3 the author brings together Tolstoi's own substantial comment.